Hypoxia-induced circPLOD2a/b promotes the aggressiveness of glioblastoma by suppressing XIRP1 through binding to HuR - Aixin Yu; Yiqi Wang; Chao Duan; Jun Qin; Miaomiao Liao; Haiyan Zhu; Junrong Lei; Jun Liu; Zehao Yang; Li Yu; Hui Gui; Jinxin Xin; et al. (Communications Biology)
Abstract Hypoxia is a common feature of glioblastoma (GBM). Circular RNAs (circRNAs) are identified as regulators in cancers. However, the role of circRNAs in GBM remains elusive. Here, circPLOD2a and circPLOD2b, spliced from the same parental gene PLOD2, are identified as hypoxia-responsive circRNAs. Overexpression of circPLOD2a and b enhance while knockdown inhibit GBM cell aggressiveness. The protein partners and downstream molecules were investigated by RNA-pulldown, mass spectrometry and RNA-seq. Mechanistically, HIF1α induces the expression of circPLOD2a and b, which competitively bind to HuR, causing a degradation of XIRP1 in vitro and in vivo. Clinical data demonstrate circPLOD2a and b are highly expressed in GBM negatively correlated with XIRP1, whose lower expression associates with higher glioma grade and worse prognosis. In conclusion, hypoxia-induced circPLOD2a and b are oncogenic regulators of tumour aggressiveness through attenuating the interaction between HuR and XIRP1 in glioblastoma cells and may be potential therapeutic targets for this disease.